Influence of Chromolaena odorata Mulch on Amaranthus hybridus L. Yield Under Agro-ecological Conditions of Gbado-Lite, Democratic Republic of the Congo - Molongo Mokondande Médard; Ngalakpa Ziada Héritier; Walengo Peter; Bolombe Lolue Augustin; Muhammad Ridwan; Koto-Te-Nyiwa Ngbolua (Budapest International Research in Exact Sciences (BirEx) Journal, 2023)
The aim of this study was to evaluate the effect of Chromolaena odorata mulch on the yield of Amaranth under the agroecological conditions of Gbado-Lite. The experimental design chosen was that of randomized complete blocks with 3 replications and each of these replications had 4 plots or 4 treatments. The treatments were as follows: T0: control plot (no amendment); T1: mulching at 18 kg per plot or 25 t/ha; T2: mulching at 36 kg per plot or 50 t/ha; T3: mulching at 54 kg per plot or 75 t/ha. The results show that with mulching, in the first trial, 6.7; 8.8; 16.5 tons per hectare were obtained; however, in the second trial, or by exploiting the residual effects, 1.8 tons per hectare were obtained; 15; 18.3; and 37.1 respectively for the control plots; plots mulched with 25 t/ha of Chromolaena odorata; with 50 t/ha of C. odorata and with 75 t/ha of C. odorata. The experiment demonstrated that mulching improves the yield of amaranth and especially its residual effects on the crop.